Vancomycin variable Enterococci in the Netherlands (2018–2023) and the mechanism of resistance induction - Christian J. H. von Wintersdorff; Milika Roelofsen; Linda Versteegh; Yassin Benyahya; Casper Jamin; Marlies Mulder; Guido J. H. Bastiaens; Maurits P. A. van Meer; Jacky Flipse (PLoS ONE, 2026)
Enterococci are common human commensals but can cause severe infections in immunocompromised patients. Enterococcus faecium is a notable example, capable of acquiring resistance to multiple antibiotics, including the critically important drug vancomycin. Such strains, known as vancomycin-resistant E. faecium (VRE), are routinely detected in clinical laboratories using phenotypic assays. However, some isolates carry vancomycin resistance genes yet remain phenotypically susceptible; these are termed vancomycin variable enterococci (VVE). Because phenotypic assays may fail to identify VVE, patients treated with glycopeptides risk developing undetected VRE infections. VVE have been reported in Scandinavia and Japan, but their prevalence in the Netherlands remains largely unknown. To address this gap, two large Dutch clinical microbiology laboratories collaborated to screen enterococcal isolates for vancomycin resistance genes using molecular assays. Among 477 isolates tested, six carried van genes while remaining vancomycin-susceptible. Three of these subsequently developed vancomycin resistance in vitro . All three were Enterococcus faecium ST117 strains carrying a chromosomal vanB2 operon, likely linked to the same outbreak. Genomic analysis revealed three mutations in the van operon regulator proteins: vanR (T189K) and vanS (G253C, L282V). We conclude that: (1) VVE are present in the Dutch population and may spread between patients; (2) VVE can develop into VRE upon vancomycin exposure; (3) specific mutations in regulatory proteins may underlie this phenotype; and (4) diagnostic policies should balance the low prevalence of VVE against their potential to cause severe complications, using sensitive molecular tests when appropriate. Our findings emphasize the importance of surveillance in revealing hidden threats and guiding clinical microbiology strategies, particularly with respect to VVE as precursors of VRE.